Sena koncepcja rozwoju jako wolności a idea "sustainable development" - Płachciak, Adam (Annales. Etyka w Życiu Gospodarczym, 2010)
Contemporary world on one hand is a place of unknown never before abundance but on the other hand it is a place where so much poverty, unsatisfied people’s needs, destabilization of natural and socio – economical systems has been happening. Neglecting human rights and basic political needs are the most important threats for development. The idea of sustainable development, playing one of the meaningful answer developmental threats requires such development which would satisfy needs of present generations without depriving future generations abilities and satisfactions of their needs. A. Sen’s concept of development, being treated as a process of widening basic civil rights and freedoms, effective-ness of social security networks play fundamental role for intellectual reflection on the idea of sustainable development.